Pengaruh Sistem Informasi Akuntansi dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Daerah - Zelda Triyani; Chara Pratami Tidespania Tubarad (Faculty of Economics and Business, 2018)
This study aim to examine the effect of accounting information system and internal control system implementation to the quality of financial report of regional device organization (OPD) in Bandar Lampung and Metro City. The population of this study is the regional services in the Bandar Lampung and Metro City Government environment (18 OPD) with 108 respondents determined by purposive sampling method. The data used are primary data collected using questionnaire through field research. Based on statistical analyzing using SmartPLS, this study found that accounting information system and internal control system implementation affects the financial reports of regional device organization (OPD) in the Bandar Lampung and Metro City Government.